Effect of size on spawning of Imbaw, Anodontia edentula (Linnaeus, 1758) - Cambel, Marianne Ponce
The effect of shell size to spawning of Imbaw. Anodontia edentula was examined. A total of 120 clams with shell length ranging from 34.90 to 68.20 mm were collected. Basing on shell length, 3 class sizes were used group these clams, namely : < 45 mm, 45-50 mm, and > 50 mm. Thirty-five percent of theclams had shell length of < 45 mm, 21.7% in the range of 45-50 mm, and 43.3% had shell length of > 50 mm. Overall result showed that a high percentage of the clams in the range of 35 to 50 mm responded to spawning induction.